Social entrepreneurship study of sakola motekar ciamis - Natechnoury, Muhammad Heykal; Maryunani, Salfitrie Roos (Journal of Business and Management, 2020)
Abstract. In conducting social entrepreneurship, it is inseparable from community participation in the area where the social entrepreneurship is located. One example is Sakola Motekar which is in the Ciamis area. Sekola Motekar itself has only been established for two years, but from preliminary observations the researcher shows that the people there are very motivated to participate in the activities held by Sakola Motekar. In contrast to other social entrepreneurs who encounter problems in society who are less enthusiastic. This research wanted to find out what motivated the people there to articipate in the activities of Sakola Motekar. Researchers used a qualitative approach in this study. When collecting data, the researcher used the ethnographic method by observing participation and interviewing the surrounding community who participated in the Sakola Motekar activity for eight days. Researchers also conducted interviews with the founder of Sakola Motekar. In analyzing the data, this study used a case study method. The result of this research is that the community is motivated to take part in Sakola Motekar activities because they feel that these activities can help them meet their needs or solve their problems. Furthermore, Sakola Motekar also applies a guidance system with a humanistic approach so that people feel comfortable in participating in Sakola Motekar activities. The founder of Sakola Motekar also wants to actualize himself by running Sakola Motekar according to the author's analysis. In the future, it is hoped that there will be future research that will be able to examine more deeply the motivation of the community to participate in social entrepreneurship activitiesKeywords: social entrepreneurship, motivation, self-actualization, rural community